The Dragon Tree Supplementary Reading Material - Hunt, Roderick (China Oxford University Press, 2012)
In The Dragon Tree, Biff and Chip visit the library and borrow a book about dragons. That night, the magic key glows, and it takes them$1 (Balong with Kipper and Floppy$1 (Binto the storybook world. They find themselves in a mysterious land near a tree with a dragon living in it. When the dragon wakes up and chases them, the children run for safety. Luckily, the magic key glows again just in time, and they escape back home.s
This imaginative story blends reading with adventure, encouraging children to explore books and storytelling. It highlights the power of imagination and the fun that books can bring$1 (Bboth in and out of the classroom.s